Fabrication, DFT modeling, and photoelectronic characterizations of novel pyridinylcarbonylquinoline for promising potential energy conversion - Magdy A. Ibrahim; Shimaa Abdel Halim; N. Roushdy; Al-Shimaa Badran; Emad M. Ahmed; A.A.M. Farag (Journal of Materials Research and Technology, 2021)
In the current exploration, an innovative 3-[(3-Cyano-1,2-dihydro-2-oxopyridin-5-yl) carbonyl]-1-methyl-4-hydroxyquinolin-2(1H)-one (CPCMHQ) structure was synthesized by condensation reaction and prepared as thin films for the first time in a simple, easy, and efficient methodology. Experiments and simulation results were used to investigate the structure and distinctive optical properties for optoelectronic applications. FT-IR spectroscopy was used to perform the vibrational spectral analysis, and the full computed vibrational analysis was made based on the potential energy distribution (PED). The outcome of the potential energy surface (PES) scan confirms that the CPCMHQ molecule has two alternative configurations, with the S1 form being the most stable for minimal energies. Density functional theory (DFT/B3LYP) was used to measure the energies using the 6-311++G (d,p) basis set. Furthermore, electronic absorption spectra in polar and non-polar solvents were considered, and the assignment of the observed bands was addressed using TD-DFT calculations. The optical band gap and other dispersion parameters of the films were determined using optical spectroscopy, which was crucial in the development of photodiode devices. Using the most accessible transitions, the optical band transitions of CPCMHQ were examined, and the direct optical gap was revealed to be 2.30 eV. In addition, the J-V properties of CPCMHQ film-based devices under various illumination indicates that photoresponsivity of CPCMHQ film-based devices increases as the reverse bias is increased, reaching the highest limit at 20 mW/cm2 for incident power. The prepared devices' photoresponsivity demonstrates that they can be used as photodetector devices.